The undergraduate dissertation as a reflection of education for sustainability and professional identity: the faculty of education of Bilbao. Issue 6 (8th June 2021) - Idoiaga Mondragon, Nahia; Axpe Saez, Inge; Berciano, Ainhoa
Abstract : Purpose: The undergraduate dissertation (UD) can be considered to be a reflection of the influence of the sustainable developmental goals (SDG) and the professional identity of the students. The purpose of this paper is to analyse the extent to which the topics of the UD reflect the SDG, considering, moreover, that they may be related to the professional identity developed by the students throughout the degree. Design/methodology/approach: This work researches the topic of 308 UDs graded as "Excellent" in the Faculty of Education of Bilbao (FEB), using a lexical analysis method. Findings: The results show two main branches: one associated with Childhood and Social Education Degrees (related to gender equality and socio-educational transformation); and another linked to the Primary Education Degree (language learning, innovation and new technologies). These analyses show the influence of the 5th (40.8%) and 4th (38.4%) SDGs in the topics chosen for the UDs. Research limitations/implications: The findings provide valuable insights into the current state of Education for Sustainable Development in the Faculty, but should be complemented with an analysis of the topics of all the UDs, to have a more real vision of the situation. Originality/value: This study analyses, for the first time, the topics of the UDs from the perspective of sustainability, taking into account the dissertations that reach a standard of excellence in the FEB. These results provide relevant information that can be very helpful to detect the specific needs for the design and implementation of an awareness-raising action that will lead to working on sustainability in a transversal way in the education degrees of the FEB.